Relative biological efficiency of protons at low and therapeutic doses in induction of 53BP1/γH2AX foci in lymphocytes from umbilical cord blood. (September 2013) - Sorokina, Svetlana; Markova, Eva; Gursky, Jan; Dobrovodsky, Jozef; Belyaev, Igor
Abstract: Purpose : In order to evaluate DNA damage induced by protons at low and radiotherapeutic doses at the therapeutic proton complex at Ružomberok, Slovak Republic, lymphocytes from umbilical cord blood (UCB) of the same four probands were irradiated in the dose range of 1–200 cGy with γ-rays and protons (200 MeV, irradiation in the Bragg peak). Materials and methods : DNA repair γH2AX/53BP1 foci were analyzed by fluorescent microscopy and flow cytometry. Results : Statistically significant effects of radiations were detected by fluorescent microscopy at all doses higher 1 cGy. Almost all distributions of foci in irradiated cells fitted to the Poisson distribution. In general, there was no difference in the levels of γH2AX and 53BP1 foci in irradiated cells. Flow cytometry was less sensitive and detected radiation induced effects at doses of 50 cGy and higher. Factorial analysis of variance in the whole studied dose range has shown no significant effect of radiation quality on number of γH2AX and 53BP1 foci. The ratio of proton-induced foci to γ-ray-induced foci was 0.86 ± 0.16 (53BP1) and 0.99 ± 0.34 (γH2AX) as measured by fluorescent microscopy and 0.99 ± 0.16 (γH2AX) as measured by flow cytometry at the radiotherapeutic dose of 2 Gy. Conclusions : Both flow cytometry and fluorescent microscopy indicated that the average value of relative biological efficiency (RBE) at radiation doses ≥ 20 cGy was about 1.0. Our data that RBE increased at low doses ≤ 20 cGy are relevant both to the development of treatment modalities and exposures that take place during space exploration and should be verified by further studies.